METHODOLOGICAL FOUNDATIONS OF TEACHERS' USE OF GENERATIVE ARTIFICIAL INTELLIGENCE SERVICES IN TEACHING NATURAL AND MATHEMATICAL SCIENCES - Kovalenko, Valentyna; Marienko, Maiia (Physical and Mathematical Education, 2025)
The article examines the methodological principles of teachers' use of generative artificial intelligence (GAI) services in teaching science and mathematics. Scientific publications on teachers' use of generative artificial intelligence services in the educational process, particularly in teaching science and mathematics, are analyzed. The methodological principles of teachers' use of GAI services in teaching science and mathematics, which consist of teaching science and mathematics using GAI, forms of teaching science and mathematics using GAI, and teaching aids, are determined.Formulation of the Problem. For this study, it is essential to present the problem of determining the methodological principles of teachers using generative artificial intelligence services in teaching natural and mathematical subjects.Materials and Methods. A set of methods was used: analysis, systematization, generalization of scientific sources, analysis of scientific publications of domestic and foreign scientists, regulatory documents, generalization of own experience, etc. Based on the prognostic approach, ways of further scientific research were determined on teachers' use of generative artificial intelligence services in teaching natural and mathematical subjects.Results. The study determined the methodological principles of using generative artificial intelligence services by teachers in teaching natural and mathematical subjects, which consist of methods of teaching natural and mathematical subjects using generative artificial intelligence, forms of teaching natural and mathematical subjects using generative artificial intelligence, and teaching aids. Conclusion. The use of GAI in teaching science and mathematics contributes to the personalization of education, increasing student motivation and improving the visualization of educational material, especially in the STEM field. However, the effective implementation of GAI requires scientifically sound methodological approaches, legislative regulation, and increasing the digital competence of teachers, in particular regarding the use of AI in the educational process. It is essential to combine traditional teaching methods with GAI and adhere to ethical principles, particularly integrity and protection of personal data. The teacher remains a key figure in the educational process, fulfilling the role of a mentor and developing students' critical thinking.
Keywords: methodological foundations; teachers; GAI services; educational process; natural and mathematical sciences